Pengaruh Temperatur Artificial Age Terhadap Kekerasan, Kekuatan Luluh dan Kerapatan Dislokasi Pada Paduan Al97,11Mg1,52Si0,86Zn0,51 - Budiarto Djono Siswanto (Universitas Medan Area, 2021)
The dislocation density, micro lattice strain, crystal size, microstructure and hardness of T6 heating treatment have been carried out with variations in temperature of artificial age in Al97,11Mg1,52Si0,86Zn0,51 alloys. The Al97,11Mg1,52Si0,86Zn0,51 alloy sample was made with granular metallurgy and then T6 was heated (solid solution heating at 530 0C for 1 hour and temperature variations of artificial age 1400C, 1700C, and 2000C and time for 1 hour). The hardness test results showed that the Al97,11Mg1,52Si0,86Zn0,51alloy increased due to variations in artificial age temperatures. Microstructure observation shows hypoeutectic structure consisting of primary aluminum dendrite and eutectic mixture of Al97,11Mg1,52Si0,86Zn0,51. The results of the analysis of dislocation density, microstructure, and crystal size after T6 heat treatment showed that the Al97,11Mg1,52Si0,86Zn0,51 alloy. consists of the -Al phase, and the Mg2Si phase. The results of artificial age resulted in recrystallization and grain growth as evidenced by an increase in micro-strain from 25.05% to 32.83% in the Miller index (311), an increase in crystallite size from 7.6734 nm to 21.3354 nm, and a decrease in dislocation density. from 0.0624 1/mm2 to 0.0067 1/mm2 and a decrease in yield strength from 573.54 MPa to 312.65 MPa.